Composition of fish catches and environmental friendliness levels based on code of conduct for responsible fisheries (CCRF) using traditional set net fishing gear with different depths in Malela waters, Awangpone district, Bone Regency. Issue 1 (1st December 2022) - Patangngari, F; Amir, F; Najamuddin,; Jaya, I
Abstract: This study aims to describe the composition, and analysis of environmental friendliness in the waters of Awangpone district, Bone regency, in November- December 2021. This research method uses exploratory case studies and interviews with FAO Code of Conduct for Responsible Fisheries (CCRF) analysis (1995) with purposive sampling methods. The composition of the traditional set net with a depth of 1.5 meters there are 47 species with a total weight of 469.98 kg. The percentage of the most catch is milkfish and bluespot mullet. The percentage of recessive fish caught were dory snaper, and rebon shrimp. While the composition of the catch traditional set netdepth of 3 meters there are 46 species with a total weight of 151 kg. The highest percentage of catches were jarbua terapon. The percentage of recessive fish caught were fringescale sardinella, Empirang common hairfin anchovy. There are 3 categories that are environmentally friendly, namely; does not endanger fishermen, does not catch protected fish, is socially acceptable and there are 6 categories that are not environmentally friendly, namely; not selective, destroying habitat, not producing quality fish, production endangering consumers, high by-catch and negative impact on biodiversity.